Quality of life in patients early after surgery - Krivokapić Žarko L.; Stojanović Goran; Terzić Negra; Jovčić Ljiljana; Miljanović Gora; Bojović Jaroslav; Janković Slobodan M. (Vojnosanitetski Pregled)
Background/Aim. Quality of life in patients early after elective surgery is related to postoperative pain and recovery rate. The aim of this study was to compare immediate preoperative and early postoperative quality of life after three common elective surgical interventions in hospital settings. Methods. Population of this prospective cohort study included patients who underwent one of the three surgical interventions: elective laparoscopic cholecystectomy (n = 40), open inguinal hernia repair (n = 40) or excision of pilonidal sinus (n = 40). Primary outcome of the study was quality of life measured once-daily, starting from the day before surgery, and then each postoperative day. It was measured by visual analogue scale (VAS) and by Serbian translation of short questionnaire on quality of life developed by World Health Organization. Results. Postoperative quality of life dropped to the lowest level on the first postoperative day, regardless of the type of surgery. The drop was the most pronounced in physical and psychological aspects of quality of life (e.g. after cholecystectomy from 15.4 ± 2.5 to 12.5 ± 2.0, and from 15.9 ± 2.0 to 14.9 ± 2.1, respectively) while social and environmental aspects were the least affected by the surgery (e.g., after excision of pilonidal sinus from 16.3 ± 2.6 to 15.7 ± 2.1, and from 14.3 ± 2.6 to 14.1 ± 2.2, respectively). Quality of life was rapidly restored on the second postoperative day, and on the last day before discharge of the patient from hospital it surpasses preoperative level (e.g., after open inguinal hernia repair from 14.6 ± 3.6 to 15.2 ± 3.0. Conclusions. Minor elective surgical interventions are associated with only moderate (less than 25%) and short (one day) immediate postoperative decrease in quality of life, which is followed by increase on discharge from hospital to the levels, higher than preoperative one.